Simultaneous denitrification and phosphorus removal by Agrobacterium sp LAD9 under varying oxygen concentration - Ma, Tao; Qian Chen; Gui, Mengyao; Li, Can; Ni, Jinren (Applied Microbiology and BiotechnologyApplied Microbiology and Biotechnology, 2016)
Although efficient aerobic denitrification has received increasing attention, few studies have been made on simultaneous denitrification and phosphorus removal (SDPR) under aerobic condition. In this study, SDPR by an efficient aerobic denitrifier, Agrobacterium sp. LAD9, was firstly demonstrated. High nitrate and phosphorus removal rates of 7.50 and 1.02 mg L-1 h(-1) were achieved in wide range of O-2 concentration from 5.92 to 20.02 mg L-1. The N2O production would be inhibited as O-2 concentration exceeded 11.06 mg L-1, while the phosphorus removal efficiency would be generally improved with increasing O-2 concentration. N-15 mass spectrometry revealed that nitrogen removal accorded with the typical aerobic denitrification pathway, while P-31 nuclear magnetic resonance spectroscopy (P-31 NMR) indicated the fate of phosphorus to cells, extracellular polymeric substances (EPS), and polyphosphate (poly-P) of the denitrifier. EPS acted as a reservoir of phosphorus and the transformation of poly-P was dynamic and depended on initial orthophosphate (ortho-P) content. The aerobic SDPR would greatly simplify the conventional wastewater treatment processes which required separated considerations of nitrogen and phosphorus removal.